Antibacterial properties of linolenic sophorolipid and its chemically esterified methyl ester form - Reetika, Gupta; Kumar, Uma S.; Asmita, Prabhune (Research Journal of Biotechnology, 2012)
The antibacterial activity of Linolenic SL mixture (containing 80% lactone) and its methyl ester derivative against Gram positive (B. subtilis) and Gram negative (E. coli and P. aeruginosa) bacteria is reported here. Bacterial cultures were treated with increasing concentrations of Linolenic SL mixture and its methyl ester derivative and antibacterial activity was checked at different time-intervals (2, 4 and 6 hrs) using standard dilution micromethod and spread plate method. Decrease in bacterial colonies was observed with increase in concentrations of compounds as well as incubation time but the level of effectiveness varies with the compound and bacteria. The minimum inhibitory concentrations (MIC) of Linolenic SL mixture (LNNSL, containing 80% lactone) against B. subtilis, E. coli and P. aeruginosa were found to be 20, 10 and 10 mu g ml(-1) respectively. The MIC values of methyl ester form (LNNSLME) against B. subtilis, E. coli and P. aeruginosa were determined to be >20, 20 and 20 mu g ml(-1) respectively. The results suggest that Linolenic SL mixture (containing 80% lactone) as compared to its methyl ester derivative showed good antibacterial activity towards both the Gram positive and Gram negative bacteria and were found to be more potent against Gram negative bacteria.
Keywords: antibacterial activity; Bacillus subtilis; Escherichia coli; Linolenic sophorolipid mixture; Minimum inhibitory concentration; Pseudomonas aeruginosa; Sophorolipid methyl ester

New class of bacterial quorum sensing antagonists: glycomonoterpenols synthesized using linalool and alpha terpineol - Mukherji, Ruchira; Prabhune, Asmita (World Journal of Microbiology & Biotechnology, 2015)
With increasing burden of antibiotic resistant microorganism search for newer drug targets and potent drug molecules is a never ending scenario. Quorum sensing (QS), the phenomenon of bacterial cross-talk, is one such target that has captured the attention of many and has been touted as the future of new age antimicrobials. Quorum sensing has the potential to regulate a plethora of bacterial virulence phenotypes and search of molecules with powerful quorum sensing inhibitory (QSI) capacity are underway. Monoterpene alcohols like linalool and alpha terpineol have been shown to possess antimicrobial and anti-biofilm activity. However in this article we attempt to bring forth a new class of compounds, glycomonoterpenols, derived from monoterpenoids alcohols. These glycomonoterpenols have been synthesized using Candida bombicola ATCC 22214 by feeding the cells with linalool and alpha terpineol respectively as substrates in 10 % glucose, production medium. The advantage of these molecules over their parent compound is their additional surfactant like property, increased solubility and enhanced QSI potential. A variety of gram-negative bacteria capable of elaborating quorum sensing mediated phenotypes have been selected and both these glycoterpenoid derivatives have been shown to possess strong anti-QS activity.
Keywords: Alpha-terpineol; Glycomonoterpenols; Linalool; Pseudomonas aeruginosa; Quorum sensing inhibition

Role of Rhamnolipid: A biosurfactant in methane gas hydrate formation kinetics - Arora, Amit; Cameotra, Swaranjit Singh; Kumar, Rajnish; Singh, Anil Kumar; Kumar, Pushpendra; Balomajumder, Chandrajit; Laik, Sukumar (Proceedings of The First International Conference on Recent Advances in Bioenergy Research, 2016)
Naturally occurring methane gas hydrate is a vast source of methane gas which is trapped in crystalline ice-like structure present in permafrost regions and under the sea in outer continental margins. It is purposed that total amount of carbon in the form of methane hydrates is almost twice the carbon content in all the fossil fuel reserves put together, and hence these are supposed to be the future potential energy resource. This paper investigates the laboratory investigations on effect of a biosurfactant rhamnolipid on methane hydrate formation kinetics. Rhamnolipid was produced by Pseudomonas aeruginosa strain A11. The presence of P. aeruginosa has been reported in Gulf of Mexico gas hydrate samples. Biosurfactant reduced the surface tension of water from 72 to 36 mN/m with CMC of 70 mg/L. The biosurfactant dose is studied at two different concentrations in the solution at 100 and 1000 ppm. Kinetic of hydrate formation and growth is compared at 0, 100, and 1000 ppm of rhamnolipid showing that rhamnolipid acts as a hydrate promoter at these concentrations. Thus, small dosages of rhamnolipids produced by P. aeruginosa strain A11 must clearly affect the gas hydrate formation kinetics in natural sites (as in Gulf of Mexico).
Keywords: Induction time; methane hydrate; Potential energy resource; Pseudomonas aeruginosa; Rhamnolipid

Nonconventional method for drying of Pseudomonas aeruginosa and its comparison with conventional methods - Umashankar, K.; Chandralekha, A.; Dandavate, T.; Tavanandi, H. A.; Raghavarao, K. S. M. S. (Drying Technology, 2018)
In this study, preparation of dried cultures of Pseudomonas aeruginosa using nonconventional drying method, namely, low-temperature low-humidity (LTLH) drying was investigated. The effect of carrier materials (whey protein, corn starch, and trehalose) was examined one at a time and also in combinations (to explore the synergistic effect). The results were compared with those obtained using spray drying and freeze drying in terms of cell survival and dry cell powder yield. The powder samples were analyzed also for morphology, flowability, particle size, and moisture content. In LTLH drying, good cell survival was observed along with high powder yield when compared with that in spray drying. Corn starch showed the highest cell survival (91%) and powder yield (94%, w/w) among the carrier materials employed besides resulting in good cell survival (65%) even after a storage period of 6 months.
Keywords: cell survival; Encapsulation; freeze drying; Low-temperature low-humidity (LTLH) drying; Pseudomonas aeruginosa; spray drying